(untitled) (Archives of Criminology, 2009)
A series of mysterious deaths in prisons made the issue of persecution organs functioning, but first and foremost question the effectiveness of controls within the prison system, returned to the newspapers’ headines. In the large part the debate has been concerned with the safety of persons who may have important information regarding ongoing criminal proceedings. Opinions are divergent, and their authors often refer back to fundamental issues. The most important and arousing the strongest emotions ones among them are as follows: where is the limit of permitted prision isolation, and how should the special units for specific categories of offenders operate? The presented study is the result of research entitled “Wstępna ocena funkcjonowania oddziałów dla więźniów niebezpiecznych” (“Introductory assessment of wards for particularly dangerous criminals”) which I carried out in 2007-2008. In the research, I examined the subject of the borders of the prison isolation, with particular emphasis on the effects of its escalation, for those who are the subjects, and for those who are executors of enhanced isolation alike. The research consisted of 10 case studies carried out on prisoners, who stayed in the special prison units with a very high degree of isolation for the longest time. Their period of stay ranged from 7 to 14 years. Penitentiary records of these individuals and the material gathered during the in-depth interviews were analysed. In addition to the presentation of the data collected during the research also contains an attempt to present a useful analytic scheme to describe and understand the functioning of this segment of the prison system, which is responsible for the isolation and control of the most dangerous criminal offenders and the most recalcitrant prisoners. The unit analysed was, so-called N ward, treated as an element of the prison culture and culture in general. The primary data source is the materials and documents related to the functioning of this segment of the prison system and the awareness of individuals participating in this social phenomenon. The latter is consistent with the assumptions of humanist criminology, in which an individual experience is a key vehicle for knowledge of the culture, and the knowledge should be searched there. The essence of this approach to the study of social phenomena is a recommendation by F. Znaniecki to study it with “the humanistic factor.” The study reconstructed the origins of wards with a high degree of isolation and it systemic rationalisation. The information collected, justify the hypothesis that the system of N wards in Poland was not prepared well enough. Ultimately there are 16 branches and with over more than 400 specially protected places of imprisonment created, despite the considerable cost, only because they were presented to decision-makers as one of the key instruments to combat the organized crime.